Metachromatic Leucodystrophy: A Case Report - Bastola, Ramchandra; Shrestha, Shree Krishna; Ghimire, Amrita; Ghimire, Sunita (Journal of Karnali Academy of Health Sciences, 2020)
Metachromatic leukodystrophy (MLD) is a rare autosomal recessive inherited disease, which is caused by a deficiency in the enzyme activity of Arylsulfatase A (ARSA). Deficiency of this enzyme results in intralysosomal storage of sphingolipid cerebroside 3-sulfates (sulfatides), which are abundant in myelin and neurons. Demyelination and neurodegeneration, causing multiple and ultimately lethal neurological symptoms is the hallmark of MLD. Here we report a case of 29 months old female child presented with regression of neurological development in a decerebrate posture. Though it is a rare disease of frequency 1/100,000 live birth, typical history and brain imaging is being reported here.